Typologies of familial space in family firms - Evans Korang Adjei (Regional Studies, Regional Science)
Over the years, family business and regional science scholars have developed an interest in exploring and understanding the relationship between the two research fields, typically, on how they influence each other. In this article, we build on the family business and the regional context to question and explore how family firms are locally embedded. We argue that the importance of local embeddedness of family firms cannot be fully understood without untangling how and what family firms are locally embedded in. Drawing on the relational spatial ontology and familial factors, and within the regional development framework, we propose typologies of family firms’ relational spaces, thereafter, familial spaces – cognitive familial space, institutional familial space, social familial space, organisational familial space and clientele/communal familial space. Where we define familial spaces as the relational networks of varied functional relationships enabled by familial factors at the disposal of family firms to explore. Based on a multidisciplinary perspective, we offer a specification of familial space and explore how the regional context and family governance system can influence the familial spaces. We maintain that family firms whose resources and productive activities are anchored in specific local places, and who themselves are locally attached, may be more likely than any other organisational type to influence familial spaces to influence their (non) economic goals. We propose suggestions for future research.